Canine spinal peripheral nerve sheath tumours in 18 dogs (2014–2023): surgical management and long-term outcomes - Deacon, Jonathan; Bongers, Jos; Stalin, Catherine (Frontiers in Veterinary Science, 2025)
Spinal peripheral nerve sheath tumours (PNST) commonly manifest as chronic pain, lameness, and paresis in dogs, and these conditions typically prove resistant to medical management. These tumours present significant surgical challenges due to their anatomical location and the complexity of achieving complete margins whilst minimising post-operative morbidity and complications. This single-centre retrospective study evaluated surgical outcomes in 18 dogs with histologically confirmed PNST treated between 2014 and 2023, examining the effectiveness of both amputation and compartmental resection approaches. An analysis revealed an overall median survival time (MST) of 326 days (range: 28–1,374 days), with three patients remaining alive at study conclusion. Notably, patients achieving R0 proximal margins demonstrated significantly better outcomes with longer overall survival times (range: 311–1,374 days, mean 841 days, median 850 days) compared to those with R1 margins (range: 28–1,357 days, mean 346 days, median 217 days). These findings demonstrate that surgical interventions, particularly when achieving non-infiltrated proximal margins, can provide meaningful improvements in both patient comfort and survival time for dogs affected by PNST.